Savvy - Law, Ingrid, 1970- (New York : Dial Books for Young Readers, 2008)
Recounts the adventures of Mibs Beaumont, whose thirteenth birthday has revealed her "savvy"--a magical power unique to each member of her family--just as her father is injured in a terrible accident.
Wilson's Children, October 2010.
Wilson's Junior High School, January 2010.
School Library Journal, May 2008.
Book Links (A.L.A.), January 2009.
Booklist starred, May 2008.
Book Links-starred, July 2008.
Keywords: Magic -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Voyages and travels -- Juvenile fiction; Magic -- Fiction; Brothers and sisters -- Fiction; Voyages and travels -- Fiction; Magic -- Fiction; Siblings -- Fiction; Magic -- Fiction